2021
DOI: 10.1007/s10899-021-10072-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Profile Segmentation in Online Lottery Gambling Utilizing Behavioral Tracking Data from the Portuguese National Lottery

Abstract: The present study is the first to examine account-based tracking data of Portuguese online lottery players comprising the gambling activity of all active players over a one-year period (N = 154,585). The main research goal was the identification of groups or segments of players by their engagement levels (high, neutral, low) and to assess preferences in product category with the use of CHAID (Chi-Square Automatic Interaction Detection) segmentation models, based on expenditure and sociodemographic variables. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…In the practice of gambling, in particular online lotteries it was found that age affects the set bet amount, the higher the age of the bettor the more bets are given. (Chagas et al, 2021) One form of gambling that is commonly done by the public is in the form of lotteries, football bets, virtual race bets, slot machines, digital games and scratch cards (Bunn et al, 2021;Hundric et al, 2021;McGrath et al, 2018). Gambling is classified as one of the forms of dependence, that is, pantological addiction without chemical substances.…”
Section: Gaming As a Means Of Gamblingmentioning
confidence: 99%
“…In the practice of gambling, in particular online lotteries it was found that age affects the set bet amount, the higher the age of the bettor the more bets are given. (Chagas et al, 2021) One form of gambling that is commonly done by the public is in the form of lotteries, football bets, virtual race bets, slot machines, digital games and scratch cards (Bunn et al, 2021;Hundric et al, 2021;McGrath et al, 2018). Gambling is classified as one of the forms of dependence, that is, pantological addiction without chemical substances.…”
Section: Gaming As a Means Of Gamblingmentioning
confidence: 99%